Promoting local knowledge on Tacca leontopetaloides (L.) Kuntze, a neglected and underutilized wild food plant for enhancing food security - Bondé, Loyapin; Hien, Bossila Séraphin; Bougma, Pawend-taoré Christian; Da, Sié Sylvestre; Ouédraogo, Oumarou; Boussim, Joseph Issaka (Ethnobotany Research and Applications, 2026)
Background: Tacca leontopetaloides is a wild food geophyte used by local communities as famine food, with significant contribution to people subsistence during food crisis events. Local ecological knowledge and use of the species are poorly documented leading to knowledge loss and underutilization of the species. This study explored local knowledge on the species, including ecology, traditional processing technique, use level, barriers to its valuation, and domestication perspective. Methods: A stratified sampling design based on climatic zones and people ethnicity was adopted for ethnobotanical investigations. Semi-structured interviews were conducted from October to December 2022, with 224 local people from five ethnic groups residing in two contrasting climate zones in Burkina Faso. The main information collected included people’s socio-cultural traits, use knowledge and ecology of the species, barriers to the species domestication, traditional processes for starch flour extraction from tubers, and people’s willingness to domesticate the species. Results: The results showed that 93.96% of the informants know the species botanically, but only 35.27% use it in practice as a food species. Practical use was significantly influenced by climate zone (p ˂ 0.0001) and people’s ethnicity (p = 0.003737). Six habitats were cited as suitable for the species occurrence, with under tree canopy (37.02%) as the main one. Ecological knowledge was also significantly affected by people’s ethnicity (X² =37.22; p = 0.00021) and climate zone (X² =88.66; p ˂ 0.0001). Ignorance of the species’ edibility (48.19%) and limited practical skills on tuber processing technique (28.31%) were listed as the main barriers to the species valuation. Only 16.52% of the informants have practical skills in tuber processing (starch extraction). For the species domestication, 80.83% of the informants testified their willingness to domesticate T. leontopetaloides. Conclusions: Our findings will help for securing the long-term use of T. leontopetaloides and enhance food security. To this end, we recommended a large-scale awareness and people training on tuber processing techniques. Keywords: Domestication; Local ecological knowledge; Barriers; Food security; Ethnicity